2018
DOI: 10.3892/ijo.2018.4665
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin‑binding protein 1A mutation‑positive Helicobacter�pylori promotes epithelial‑mesenchymal transition in gastric cancer via the suppression of microRNA‑134

Abstract: Evidence suggests that Helicobacter pylori (H. pylori) is not only the main cause of gastric cancer (GC), but is also closely associated with its metastasis. One of the major virulence factors in H. pylori is the cytotoxin-associated gene A (CagA). With the growing proportion of amoxicillin-resistant H. pylori strains, the present study aimed to explore the effects of CagA- and penicillin-binding protein 1A (PBP1A) mutation-positive H. pylori (H. pyloriCagA+/P+) on GC cells, and its clinical significance. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Moreover, CagA is highly associated with the induction and further progression of the EMT within the gastric mucosa, which is associated with greater invasiveness properties. The process is stimulated via several CagA-related mechanisms such as the downregulation of programmed cell death protein 4 (PDCD4), induction of cancer stem cell-like properties, reduction in glycogen synthase kinase 3 (GSK-3) activity, overactivation of fibroblasts, suppression of microRNA-134, altering the yes-associated protein (YAP) pathway, or Afadin protein downregulation [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Particular cagA genotypes present different severity of enhanced IL-8 and cytotoxin production, inflammatory responses, or apoptosis in gastric epithelial cells.…”
Section: Cytotoxin-associated Gene Amentioning
confidence: 99%
“…Moreover, CagA is highly associated with the induction and further progression of the EMT within the gastric mucosa, which is associated with greater invasiveness properties. The process is stimulated via several CagA-related mechanisms such as the downregulation of programmed cell death protein 4 (PDCD4), induction of cancer stem cell-like properties, reduction in glycogen synthase kinase 3 (GSK-3) activity, overactivation of fibroblasts, suppression of microRNA-134, altering the yes-associated protein (YAP) pathway, or Afadin protein downregulation [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Particular cagA genotypes present different severity of enhanced IL-8 and cytotoxin production, inflammatory responses, or apoptosis in gastric epithelial cells.…”
Section: Cytotoxin-associated Gene Amentioning
confidence: 99%
“…Interestingly, PVT1 is located on chromosome band 8q24.21 and is frequently co-amplified with MYC [ 30 , 194 ]. Additional miRNAs established to target FOXM1 in ovarian cancer are miR-134 [ 195 , 196 , 197 , 198 , 199 ] and miR-216b [ 200 , 201 , 202 , 203 ]. Interestingly, a recent report indicates that FOXM1 acts as a transcriptional regulator of several miRNA molecules in triple-negative breast cancer, which has a similar molecular profile to HGSC [ 204 ].…”
Section: Foxm1 Is Overexpressed and Activated In Ovarian Cancermentioning
confidence: 99%
“…Penicillin-binding protein (PBP) is a specialized acyl serine transferase released by H. pylori with an affinity for penicillin binding; any modifications within PBP might induce resistance to β-lactam antibiotics (amoxicillin, penicillin G, ampicillin) [197]. These mainly include either mutations or mosaics (or both) of PBP2X, PBP2B, and PBP1A [198]. It was shown that H. pylori PBPs might present unique characteristics because of several putative genes encoding PBPs.…”
Section: Penicillin-binding Protein 1amentioning
confidence: 99%